Genome-wide identification of the jumonji C domain- containing histone demethylase gene family in wheat and their expression analysis under drought stress - Wang, Xinhua; Pan, Cuili; Long, Jiaohui; Bai, Shuangyu; Yao, Mingming; Chen, Jiajing; Sun, Gang; Fan, Yalei; Wang, Zhangjun; Liu, Fenglou; Liu, Caixia; Li, Qingfeng (Frontiers in Plant Science, 2022)
Methylation and demethylation of histone play a crucial role in regulating chromatin formation and gene expression. The jumonji C (JmjC) domain-containing proteins are demethylases that are involved in regulating epigenetic modification in plants. In our study, the JmjC genes in Triticum aestivum L., Triticum turgidum L., Triticum dicoccoides L., Triticum urartu L., and Aegilops tauschii L. were identified. Phylogenetic relationship and colinearity analysis revealed that the wheat JmjC genes were conserved in A, B, and D subgenomes during evolution. Cis-acting elements analysis showed that elements related to stress response, hormone response, and light response were found in wheat JmjC genes. The expression of JmjC genes was affected by tissue types and developmental stages, and members of the same subfamily tended to have similar expression patterns in wheat. They also showed a unique expression pattern in root during PEG (Polyethylene glycol) treatment. In conclusion, comprehensive analysis indicated that three members (Tr-1A-JMJ2, Tr-1B-JMJ2, and Tr-1D-JMJ2) might be regulated by several hormones and function in the early stages of drought stress, while eight members (Tr-1B-JMJ3, Tr-4B-JMJ1, Tr-7A-JMJ1, etc.) displayed a significantly high expression after 24 h of PEG treatment, indicating a role in the later stages of drought stress. This research presents the first genome-wide study of the JmjC family in wheat, and lays the foundation for promoting the study of their functional characterization in wheat drought resistance.